HISTORICAL DEVELOPMENT OF THE HTAsiaLINK NETWORK AND ITS KEY DETERMINANTS OF SUCCESS. (18th June 2018) - Teerawattananon, Yot; Luz, Karlena; Yothasmutra, Chalarntorn; Pwu, Raoh-Fang; Ahn, Jeonghoon; Shafie, Asrul Akmal; Chalkidou, Kalipso; Tantivess, Sripen; Santatiwongchai, Benjarin; Rattanavipapong, Waranya; Dabak, Saudamini
Abstract : Objectives: The aim of this study was to describe the historical development of the HTAsiaLink network, draw lessons for other similar initiatives globally, and to analyze key determinants of its success and challenges for its future development. Methods: This study is based on the collective and direct experiences of the founding members of the HTAsiaLink Network. Data were collected from presentations they made at various international forums and additional information was reviewed. Data analysis was done using the framework developed by San Martin-Rodriguez et al. Results and Conclusions: HTAsiaLink is a network of health technology assessment (HTA) agencies in Asia established in 2011 with the aim of strengthening individual and institutional HTA capacity, reducing duplication and optimizing resources, transfer and sharing of HTA-related lessons among members, and beyond. During its 6 years, the network has expanded, initiating several capacity building activities and joint-research projects, raising awareness of the importance of HTA within the region and beyond, and gaining global recognition while establishing relationships with other global networks. The study identifies the determinants of success of the collaboration. The systemic factors include the favorable outlook toward HTA as an approach for healthcare priority setting in countries with UHC mandates. On organizational factors, the number of newly established HTA agencies in the region with similar needs for capacity building and peer-to-peer support was catalytic for the network development. The interactional aspects include ownership, trust, and team spirit among network members. The network, however, faces challenges notably, financial sustainability and management of the expanded network.